Wave number determination of Pc 1–2 mantle waves considering He++ ions: A Cluster study. Issue 9 (30th September 2014) - Grison, B.; Escoubet, C. P.; Santolík, O.; Cornilleau‐Wehrlin, N.; Khotyaintsev, Y.
Abstract The present case study concerns narrowband electromagnetic emission detected in the distant cusp region simultaneously with upgoing plasma flows. The wave properties match the usual properties of the Pc 1–2 mantle waves: small angle between the wave vector and the magnetic field line, left‐hand polarization, and propagation toward the ionosphere. We report here the first direct wave vector measurement of these waves (about 1.2 × 10− 2 rad/km) through multi spacecraft analysis using the three magnetic components and, at the same time, through single spacecraft analysis based on the refractive index analysis using the three magnetic components and two electric components. The refractive index analysis offers a simple way to estimate wave numbers in this frequency range. Numerical calculations are performed under the observed plasma conditions. The obtained results show that the ion distribution functions are unstable to ion cyclotron instability at the observed wave vector value, due to the large ion temperature anisotropy. We thus show that these electromagnetic ion cyclotron (EMIC) waves are amplified in the distant cusp region. The Poynting flux of the waves is counterstreaming with respect to the plasma flow. This sense of propagation is consistent with the time necessary to amplify the emissions to the observed level. We point out the role of the wave damping at the He++ gyrofrequency to explain that such waves cannot be observed from the ground at the cusp foot print location.